The Cause of Seamless Integration: Revisiting the Dual Authorship of the Kāvyaprakāśa - Bronner, Yigal (JAOS, 2023)
This paper revisits the longstanding tradition concerning the dual authorship of the Light on Literature (Kāvyaprakāśa), the dominant treatise on Sanskrit poetics in the second millennium CE. The discussion focuses on one case study, a brief comment dismissing the ornament "cause" (hetu), found in the latter part of chapter 10 in the portion traditionally attributed to Mammaṭa's successor Allaṭa (aka Alaka). This passage is analyzed in the broader context of the Light's discussion of semantic capacities (chapter 2), suggestion (chapter 4), and other ornaments (chapter 10). The essay also looks at the way generations of commentators have dealt with this topic and the potential inconsistencies in its treatment in the Light. The paper thus throws light on the question of the work's overall integration, seamless or not so seamless, both in its genetic and receptive histories.